2019
DOI: 10.17269/s41997-019-00180-w
|View full text |Cite
|
Sign up to set email alerts
|

Supervised inhalation is an important part of supervised consumption services

Abstract: Setting The first regulated supervised inhalation site (safer smoking room) in North America has opened in Lethbridge, Alberta, as part of a supervised consumption site addressing all routes of consumption. When designing the service, we felt it was important to accommodate not just injection drug use but also inhalation because (1) it is not the method of drug use that kills but the drug itself, (2) all people who use drugs deserve service regardless of their mode of use, and (3) people who use drugs should h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The level of reported detail on SCS varies considerably by jurisdiction, and appears to be impacted by political climates [80]. In recent years, an increasing number of Canadian SCS permitted intranasal and oral consumption [81], and Lethbridge, Alberta opened the first SCS in North America to permit all routes of consumption (injection, inhalation, intranasal, oral) in February 2018 [17]. However, limited data has been published on these SCS to date [82].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of reported detail on SCS varies considerably by jurisdiction, and appears to be impacted by political climates [80]. In recent years, an increasing number of Canadian SCS permitted intranasal and oral consumption [81], and Lethbridge, Alberta opened the first SCS in North America to permit all routes of consumption (injection, inhalation, intranasal, oral) in February 2018 [17]. However, limited data has been published on these SCS to date [82].…”
Section: Discussionmentioning
confidence: 99%
“…People engaged in public non-injection drug consumption report experiencing violence when using in public areas, from police and others [ 15 , 16 ]. SCS that incorporate non-injection routes of consumption have the potential to reduce the risk of these harms through provision of emergency medical care, a safe environment, and sterile smoking and intranasal consumption supplies [ 17 20 ]. Additionally, providing access to SCS that incorporate non-injection routes of consumption may reduce the risk of transitioning to injection [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of clients (n = 654) and related service visits (March -June 2018) of a new supervised consumption service comprising multiple routes of administration in Lethbridge, Alberta, increasing monthly client ratesfrom 60 to 70% -utilized inhalation services. 82.0% of inhalation service visits involved methamphetamine, 11.3% opiates and 3.1% crack-cocaine; in the injection facility, 57.1% involved opiates, 29.9% methamphetamine, 12.4% 'speedballs' (fentanyl/methamphetamine combination) [71]. Furthermore, recent key informant data on supervised consumption services in Alberta suggested that the most commonly used drug "changed from opioids and cocaine, to methamphetamine" among service users; in addition, many were "polydrug users and were consuming both opioids and methamphetamine" (p.13) [72].…”
Section: Canada-based Datamentioning
confidence: 99%
“…DCTs are also often implemented in supervised consumption sites (SCS), which themselves serve as overdose prevention interventions. Within North America's limited number of SCSs, these have largely focused on injecting and only one regulated supervised inhalation site exists [25], rendering people who smoke stimulants vulnerable to overdose and other harms associated with unsupervised drug use.…”
Section: Supporting Safer Stimulant Use Through a Safe Supplymentioning
confidence: 99%